Gambaran Kepedulian Orang Tua Terhadap Pendidikan Remaja di Jorong Sungai Cubadak Kecamatan Akabiluru Kabupaten Lima Puluh Kota - Yelvina Yelvina; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the success of teenage education in Jorong Sungai Cubadak Kecamatan Akabiluru Kabupaten Lima Puluh Kota. This research also purpose to describe parenting care about teenage education with: (1) Fullfilled for the requirement (2) Giving advice and motivation (3) Supervise process of education (4) Process guidance. This research use descriptive quantitative approach. For supporting this approach, researcher take a quesioner and involve with 50 % from 47 teenage partisipants . Data will be submit and analyse with percentage. Based on this research, show some indication that: (1) parenting care about teenage education showed by participating to fullfill for the requirement was high (2) Parenting care about teenage education showed by participating to give a motivation was high (3) Parenting care about teenage education showed by partisipating to supervise process of education was high (4) Parenting care about teenage education showed by participating in guidance process of education was high. Keywords: Parenting Care, Teenage Education